Place-based consequences of person-based transfers: Evidence from recessions - Brad Hershbein; Bryan A. Stuart (W.E. Upjohn Institute for Employment Research, 2022)
This paper studies how government transfers respond to changes in local economic activity that emerge during recessions. Local labor markets that experience greater employment losses during recessions face persistent relative decreases in earnings per capita. However, these areas also experience persistent increases in transfers per capita, which offset 16 percent of the earnings loss on average. The increase in transfers is driven by unemployment insurance in the short run, and medical, retirement, and disability transfers in the long run. Our results show that nominally place-neutral transfer programs redistribute considerable sums of money to places with depressed economic conditions.
Keywords: E32; H50; R12; R28; 330; recessions; safety net; government transfers; demand shocks; local labor markets; event study